How authentic leadership promotes individual performance: Mediating role of organizational citizenship behavior and creativity. Issue 9 (19th November 2018) - Ribeiro, Neuza; Duarte, Ana Patrícia; Filipe, Rita
Abstract : Purpose: The purpose of this paper is to provide a more comprehensive understanding of how authentic leadership (AL) can affect individual performance through creativity and organizational citizenship behavior (OCB)'s mediating roles. Design/methodology/approach: The sample included 177 leader-follower dyads from 26 private and small and medium-sized organizations. Followers reported their perceptions of AL, and leaders assessed each follower's level of creativity, individual performance and OCB. Findings: The findings show that AL has a positive impact on OCB (i.e. altruism, sportsmanship, civic virtue, conscientiousness and courtesy), employee creativity, and individual performance. Creativity partially mediates the relationship between AL and individual performance. Some dimensions of OCB, namely, altruism, civic virtue and courtesy, also play a mediating role in this relationship. Research limitations/implications: Additional studies with larger samples are needed to determine more clearly not only AL's influence on individual performance but also other psychosocial variables affecting that relationship. Practical implications: Organizations can increase employees' creativity, OCB and individual performance by encouraging managers to adopt more AL styles. Originality/value: This study is the first to integrate AL, creativity, OCB and individual performance into a single research model, thereby extending previous research. The study also used a double-source method to collect data (i.e. leader-follower dyads) to minimize the risk of introducing common-method variance.